Study the Control Analysis Methods on a Direct Current Motor - (:unkn) unknown (IEEE, 2020)
This study focuses on the control analysis methods used to implement mathematical equations for Direct Current Motor parameters for emphasizing the influential and proper analysis methods, computer application and visualization is very significant. The control analysis methods are highly rigorous, stressful and complex subjects for students to conceive, comprehend and to easily reach solutions. This study involves step by step examinations of the analysis methods through computer simulations to provide a comprehensive account of direct current motor parameters through mathematical equations by using Mathematica language. Additionally, this study also looks at the implications of gaining an understanding of analysis models such as the step response, Bode diagrams, Nyquist and Nichols plots for motors and their control units to develop a deeper level of understanding.
Keywords: direct current motor; transfer function; analysis methods; education; control; Mathematica